Global health governance in the sustainable development goals: Is it grounded in the right to health?. Issue 1 (January 2017) - Van de Pas, Remco; Hill, Peter S.; Hammonds, Rachel; Ooms, Gorik; Forman, Lisa; Waris, Attiya; Brolan, Claire E.; McKee, Martin; Sridhar, Devi
Abstract: This paper explores the extent to which global health governance – in the context of the early implementation of the Sustainable Development Goals is grounded in the right to health. The essential components of the right to health in relation to global health are unpacked. Four essential functions of the global health system are assessed from a normative, rights‐based, analysis on how each of these governance functions should operate. These essential functions are: the production of global public goods, the management of externalities across countries, the mobilization of global solidarity, and stewardship. The paper maps the current reality of global health governance now that the post‐2015 Sustainable Development Goals are beginning to be implemented. In theory, the existing human rights legislation would enable the principles and basis for the global governance of health beyond the premise of the state. In practice, there is a governance gap between the human rights framework and practices in global health and development policies. This gap can be explained by the political determinants of health that shape the governance of these global policies. Current representations of the right to health in the Sustainable Development Goals are insufficient and superficial, because they do not explicitly link commitments or right to health discourse to binding treaty obligations for duty‐bearing nation states or entitlements by people. If global health policy is to meaningfully contribute to the realization of the right to health and to rights based global health governance then future iterations of global health policy must bridge this gap. This includes scholarship and policy debate on the structure, politics, and agency to overcome existing global health injustices. Impact Statement: The European Union funded Go4Health research consortium researched the positioning of health in the Sustainable Development Goals providing expert commentary, policy advice, and engagement with key global, national, and local stakeholders. Go4Health critically examined national and multilateral input into the Sustainable Development Goals process, including the proposed governance structures for health. It advocated for the inclusion of human rights in the Sustainable Development Goals through a right‐to‐health framing in its analysis and advocacy. In line with the European Commission and World Health Organization, it argued that Universal Health Coverage best embodied these values and provided rigorous academic arguments, grounded in international law, and public health to support this approach. This research article aims to stimulate debate on the governance and implementation of global health policy frameworks such as the UHC2030 alliance and the High‐Level Political Forum on sustainable development. The possible impact of the research is to advance the normative thinking and development of transnational global health policies that safeguard and advance human rights while acknowledging that the current political momentum is limited. However, we believe that transnational, shared, health risks will eventually also lead to shared transnational health responsibilities. This manuscript, and other publications by Go4Health, will contribute to develop such cosmopolitan health governance frameworks.